The Role of SIMS and Information Quality in Supporting Decision Making and Employee Performance BPN Labuhanbatu District - Novi Ardaningsi; Pristiyono Pristiyono; Elvina Elvina (Journal of Applied Business Administration, 2023)
The purpose of this study was to determine the effect of the role of management information systems and information quality on the decision-making process tested partially and management information systems and information quality on employee performance at the National Land Agency (BPN) of Labuhanbatu Regency. This research started from November 2022 to March 2023 which was carried out on employees at the National Land Agency (BPN) of Labuhanbatu Regency with a population consisting of 83 State Civil Apparatus (ASN). The sampling technique uses a census technique with data collection techniques in the form of secondary data and primary data with Likert scale techniques. The data analysis technique in this study used Partial Least Square (PLS). Based on the results of research and discussion in this study, the research can be concluded as follows: 1) management information system variables have a positive and significant effect on management decision making, 2) information quality variables have a positive and significant effect on management decision making, 3) information quality system variables have a positive and significant effect on employee performance, 4) information quality variables have no positive and insignificant effect on employee performance and 5) management decision making variables have a positive and significant effect on employee performance.